Living on the edge: Herpetofauna of the buffer zone of the Parque Estadual da Serra da Tiririca, Rio de Janeiro State, Brazil - Miguel R. Ugalde; Thaylan P. Alves Salles; Amanda F. Marinho; Mara C. Kiefer (Zoologia (Curitiba))
ABSTRACT Habitat loss and fragmentation is the greatest threat to global biodiversity and is especially acute in biodiversity hotspots such as the Atlantic Forest of Brazil. Because the Brazilian fauna suffers from ongoing human impacts both inside and outside protected areas and their buffer zones, inventories of the faunal assemblages in these areas remain vital. Based on field surveys and the examination of museum specimens, we report on the herpetofauna of the buffer zone of Parque Estadual da Serra da Tiririca, located in the Brazilian state of Rio de Janeiro. Across nine sampling areas during 2017 and 2018, we documented 30 species of anurans, one caecilian, 18 snakes, eight lizards, and one crocodilian. This assemblage includes the first record for five species from the protected area. Our inventory offers fundamental information that can promote actions to maintain populations of these taxonomic groups and their habitats within and outside of this protected area.